Simulasi Desain Kontrol MPPT Sistem Photovoltaic - Puji Slamet; Subekti Yuliananda; Santoso Santoso (Muhammadiyah University, Sidoarjo, 2019)
Maximum Power Point Tracking (MPPT) modeling has been developed which is part of a photovoltaic (PV) system. This study applies an algorithm for tracking maximum power points in the photovoltaic unit as a whole. The algorithm applied to the MPPT is simulated in PROTEUS modeling to verify the proposed method, the PID control method is simulated in Matlab and Simulink. Simulation shows that changes in input current and voltage will produce different PID controls, with a PWM duty cycle of 10% to 99%.